EFFORTS TO OVERCOME THE CRIME OF THEFT OF MOTOR VEHICLE PROCEEDINGS FROM THEFT IN THE JURISDICTION OF THE BINJAI POLICE - Siti Indarwati; Tiolita Dora Br Tarigan; Wismar Azmi; Ian Wooton (Journal of International Islamic Law, Human Right and Public Policy, 2023)
This article aims to find out how to deal with the criminal act of stealing motor vehicles from theft in the jurisdiction of the Binjai Police and what sanctions are imposed on the perpetrators of this criminal act of holding. This writing is based on problems that often occur in the Binjai area and have not yet been effective in resolving legal problems. The research method used is the Empirical Juridical method with a descriptive analysis approach. The results of this research. The increase in crimes involving theft of motorized vehicles is caused by various factors, namely internal factors consisting of individual factors, economic factors and educational factors. Meanwhile, external factors that can influence it are environmental factors and technological and cultural development factors. In order to ensure that criminal acts of detention by theft do not continue to increase, it is necessary to make efforts to overcome them.